GUEST SATISFACTION IN BELGRADE RESTAURANTSIN COMPARISON TO LARGE EUROPEAN CITIES - Živadinović, Bojan (Ekonomija - teorija i praksa, 2022)
Information technologies with specialized websites (Trip Advisor, Booking, Expedia…) and social networks (Facebook, Instagram…) provide tourists with more detailed information about specific aspects of tourist offer. Restaurants, with their gastronomic offer, extend hospitality to guests and present the culture of one nation in a special way. The aim of this paper is to analyze user ratings of 42,596 European metropolitan restaurants on Trip Advisor and draw conclusions related to the satisfaction of restaurant visitors in Belgrade compared to major European cities. Prior to modeling, visitor ratings (1–5) were grouped into two categories: satisfied (ratings 4 and 5) and barely satisfied (ratings 1–3), and then the number of satisfied and dissatisfied customers was summed up for each restaurant. The probability of belonging to the aforementioned categories (satisfied/barely satisfied) was modeled using logistic regression for each city.